EFFECT OF COMPANY AGE, AUDIT QUALITY, LEVERAGE AND PROFITABILITY ON EARNINGS MANAGEMENT - Nawang Kalbuana; Adelina Suryati; Chandra Puspa Arum Pertiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to test the impact of Company Age, Audit Quality, Leverage and Profitability on Earnings management on Indonesian Stock Exchange-listed Retail and Wholesale Trading Companies for the years 2016-2020. The study used data obtained from financial statements. The trade sector, which is listed on the Indonesia Stock Exchange, is the focus population for this study. The sample selection technique used is purposive sampling with several criteria that have been determined, the sample data obtained by 18 companies with the period 2016-2020. SPSS version 25 was utilized for data analysis, and the traditional assumption test of heteroskedasticity multicollinierity, normality test, correlation and determination coefficient test, simultaneous test, and partial test were used. This research showed that company age had a significant positive impact on earnings management, audit quality had a significant negative impact on earnings management, leverage had no significant impact on earnings management and profitability had a positive impact on earnings management.